Valvular Heart Disease - Vinall, Phil (MD Conference Express, 2010)
Over the last 20 years, the use of mechanical valves for valve replacement has fallen out of favor. While the decline has been due primarily to a high incidence of thromboembolism and the risk of hemorrhage that is associated with the anticoagulants that are used to prevent thrombosis, continuous improvements in both the Ross Procedure and valvular prosthesis processing have also been factors in the drop in use of mechanical valves. This article discusses advances in both valves and implantation procedures.